Integrated Mechanistic Model of Minimal Residual Disease Kinetics With Venetoclax Therapy in Chronic Lymphocytic Leukemia. Issue 2 (6th September 2020) - Gopalakrishnan, Sathej; Wierda, William; Chyla, Brenda; Menon, Rajeev; Miles, Dale; Humerickhouse, Rod; Awni, Walid; Salem, Ahmed Hamed; Mensing, Sven; Freise, Kevin J.
Abstract : Minimal residual disease (MRD) is an important emerging clinical end point in chronic lymphocytic leukemia (CLL). The objective of this research was to develop an integrated mechanistic model to evaluate the impact of venetoclax‐rituximab combination therapy on MRD kinetics. Using data from 435 patients with relapsed or refractory CLL, an integrated model was developed and validated that accounted for venetoclax dosing and pharmacokinetics, rituximab treatment, absolute lymphocyte count, and blood and bone marrow (BM) MRD data. Simulations of venetoclax‐rituximab (six cycles) combination predicted the proportion (90% confidence interval) of patients with BM MRD below 10 −4 to be 57% (54–61%) and 63% (59–67%) at 12 and 24 months of treatment, respectively. Continued venetoclax treatment to 48 months only increased the predicted rate of negative BM MRD to 66% (63–70%). These results indicate that treatment with venetoclax‐rituximab combination for a finite 2‐year period would nearly maximize the rate of negative BM MRD (< 10 −4 ). Preliminary clinical data agree with these predictions and more long‐term follow‐up data are awaited to confirm the same.